Property of Human Bone Marrow Stromal Cells Derived From Bone Fragments Removed in Sagittal Split Ramus Osteotomy. Issue 4 (June 2016) - Yoshida, Chihiro; Yamaguchi, Satoshi; Abe, Shigehiro; Harada, Kiyoshi
Abstract : Abstract: Bone tissue engineering is in the process of making the shift from bench to bed. Organ as a cell source is important for tissue engineering. The appropriate cells should be harvested without invasiveness and ethical problems. The authors focused on mandibular cortex bone fragments removed in sagittal split ramus osteotomy as a cell source for bone tissue engineering. These bone fragments were discarded after surgery until now. Bone marrow stromal cells (BMSCs) were harvested from inside of bone fragments, which is an endosteal region. Endosteal region is known to be a hematopoietic stem cell niche and harbors osteoblasts, preosteoblasts, and mesenchymal stem cells (MSCs). Bone marrow stromal cells could be cultured easily, and grew rapidly in vitro under ordinary serum-supplemented culture condition. The expression pattern of surface markers of BMSCs was the same as that of MSCs. Bone marrow stromal cells could differentiated into multiple mesenchymal lineages (osteoblasts, adipocytes, chondrocytes, and smooth muscle cells). These results indicated the existence of MSCs in BMSCs. The osteoblastic characters of BMSCs were examined more closely. Bone marrow stromal cells showed a high alkaline phosphatase activity, and expressed osteoblastic markers (PTHr, bone sialoprotein, Type I collagen, Rnut-related transcription factor 2, and osteocalcin). In transplantation experiments, BMSCs generated ectopic bone tissues on the border of hydroxyapatite scaffold without osteogenic differentiation-inducing agents such as dexamethasone (Dex) or bone morphogenetic protein. The results of this study suggest that mandibular cortex bone fragments removed in sagittal split ramus osteotomy are a good cell source for bone tissue engineering.